Clubroot disease in soil: An examination of its occurrence in chemical and organic environments - Zakirul Islam; Quoc Thinh Tran; Motoki Kubo (Resources, Environment and Sustainability)
Clubroot is a disease in cruciferous plants caused by the soil-borne pathogen Plasmodiophora brassicae. This pathogen rapidly spreads in soil, and plant growth is inhibited by infection with spores. To reduce clubroot disease, its prevalence in Brassica rapa var. perviridis was investigated in different soil environments (chemical and organic soils). The bacterial biomass, diversity, and community structure of the soils and roots were analyzed by environmental DNA, PCR-DGGE, and 16S rRNA sequencing. Bacterial biomass and diversity in the organic soil were higher than those in the chemical soil. The disease severity of plants cultivated in organic soil was lower than that in chemical soil. The number of endophytic bacteria in the roots decreased when the plants were infected with P. brassicae in both soil types. Higher bacterial biomass in the soils and roots appeared to reduce the infection of P. brassicae.